Assessment of Heavy Metal Contamination in Surface Water of Masinga Reservoir, Kenya - Nzeve, Julius K.; Njuguna, Steven G.; Kitur, Esther C. (Journal of Natural Sciences Research, 2015)
An assessment of heavy metal contamination (Cu, Zn, Pb, Cr, Mn and Cd) in surface water of Masinga reservoir was carried out between January 2013 and December 2013. The heavy metal Concentrations were determined using atomic absorption spectrophotometer (AAS). The data obtained was analyzed using one way analysis of variance and significant differences accepted at p ≤ 0.05. Post Hoc Tukeys’ test was used to separate means. The mean metal concentrations (mg L-1) were; Cu (0.003 - 0.019), Zn (0.092 - 0.132), Pb (0.004 - 0.009), Cr (0.003 - 0.006) and Mn (0.006 - 0.146). No significant differences were observed in heavy metal concentrations in surface water among the different sites. The concentrations for all metals in surface water did not exceed the WHO recommended limit for drinking water.
Keywords: Water Quality; Heavy Metals; Contamination; Masinga Reservoir